A study on women's health information needs in menopausal age - Sadrieh Hajesmaeel-Gohari; Elaheh Shafiei; Fatemeh Ghasemi; Kambiz Bahaadinbeigy (BMC, 2021)
Abstract Menopause is a natural event experienced by women in middle age. To help women manage this event, it is important to identify their health information needs. A study specific questionnaire was used to identify menopausal women's health information needs and the resources and challenges related to finding information about menopause. A total of 301 women aged 48-55 years completed the questionnaire. Data were analysed using negative binomial regression and chi-square tests. The most frequently sought information was that related to breast cancer (n = 209, 69.5%), hot flushes (n = 200, 66.5%), cervical cancer (n = 194, 64.5%), non-hormonal therapies for menopausal symptoms (n = 192, 64%), laboratory tests (n = 189, 63%) and joint and muscle pain (n = 188, 62.5%). The main sources of information were audiovisual media (n = 171, 57%), obstetricians (n = 165, 55%), friends (n = 157, 52%), family (n = 157, 52%) and the internet (n = 153, 51%). The two main challenges were not knowing how to correctly access information (n = 115, 38%) and not being aware of reliable sources of information (n = 108, 36%). Therefore, it is essential for policymakers and decision-makers to provide reliable and accurate information to increase awareness and reduce anxiety of women experiencing menopause.